Technological Solutions for Cardiac Surgery in the Elderly - Nir, Rony-Reuven (Rambam Health Care Campus, 2013)
The current review addresses contemporary technological advances in cardiac surgery performed on octogenarian patients, namely off-pump coronary artery bypass grafting (CABG), proximal anastomosis device, routine use of intraoperative epiaortic ultrasound, proximal anastomosis without clamping, transcatheter aortic valve implantation (TAVI), and brain protection during cardiac surgery.